The Underlying Mechanisms of Psychological Resilience on Emotional Experience: Attention-Bias or Emotion Disengagement - Yi, Feng; Li, Xiaofang; Song, Xiaolei; Zhu, Lei (Frontiers in Psychology, 2020)
Psychological resilience is consisted of social resources and protective factors for individuals against negative effects, and can influence the process of meta-cognition of individuals in response to emotion feelings. However, individuals with high or low resilience may produce various emotional experiences when facing the same events. According to an emotional input–output model, the different impacts of resilience on emotional experience may be caused during the process of receiving or disengaging stages. In order to address this problem, three experiments were conducted in the present study. The Experiment 1 was designed to explore whether the positive and negative emotions were associated with higher or lower levels of resilience. The aims of Experiments 2 and 3 were to test at which stages the different emotional experiences were caused by high or low resilience of individuals. The results showed that individuals with low resilience were more likely to feel more negative and less positive emotions, and resilience was significantly negatively associated with anxiety or depression. However, there was no difference in the stage of receiving emotional information between high and low resilient individuals, but differ on their ability of disengagement from emotional information, the individuals with high resilience disengaged from both positive and negative emotional information much faster. These findings were discussed in the context of different theories about the relationship between resilience and emotional experience.